2020
DOI: 10.1097/md.0000000000022807
|View full text |Cite
|
Sign up to set email alerts
|

A nomogram for determining the disease-specific survival in invasive lobular carcinoma of the breast

Abstract: We aimed to establish and validate a nomogram for predicting the disease-specific survival of invasive lobular carcinoma (ILC) patients. The Surveillance, Epidemiology, and End Results program database was used to identify ILC from 2010 to 2015, in which the data was extracted from 18 registries in the US. Multivariate Cox regression analysis was performed to identify independent prognostic factors and a nomogram was constructed to predict the 3-year and 5-year survival rates of ILC patients based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Nomogram is a visual and individualized tool for predicting prognosis. By integrating more clinicopathological variables, nomograms can provide a more accurate prognosis than the TNM staging system [9][10][11]. At present, several nomograms about rectal cancer had been reported [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nomogram is a visual and individualized tool for predicting prognosis. By integrating more clinicopathological variables, nomograms can provide a more accurate prognosis than the TNM staging system [9][10][11]. At present, several nomograms about rectal cancer had been reported [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Nomograms have been regarded as reliable and effective tools to evaluate cancer outcomes by incorporating various pathological and clinical characteristics. It has been recognized that nomograms do better than traditional TNM staging systems in assessing the prognosis of cancer [9][10][11]. Nevertheless, there is no nomogram to predict the overall survival (OS) in young non-metastatic RC patients after curative resection.…”
Section: Introductionmentioning
confidence: 99%
“… 26 It is generally believed that AUC greater than 0.8 is of great diagnostic value, and the specific predictive value should be evaluated in combination with clinical practice. Meanwhile, The nomogram was subjected to bootstrapping validation (1000 bootstrap resamples) to calculate an optimism-corrected Harrell’s C statistic (C-index) 19 , 27 in the development group and the validation group, respectively. Calibration degree is an important index to evaluate the accuracy of disease risk model in predicting the probability of individual future outcome events.…”
Section: Methodsmentioning
confidence: 99%
“… 15–17 among which building nomogram is one of the hottest research directions. In the latest research, 15 , 18 , 19 the use of nomogram prediction has shown good performance.…”
Section: Introductionmentioning
confidence: 99%
“…Nomograms have been regarded as reliable and effective tools to evaluate cancer outcomes by incorporating various pathological and clinical characteristics. It has been recognized that nomograms do better than traditional TNM staging system in assessing the prognosis of cancer [12][13][14]. Nevertheless, there is no nomogram to predict the overall survival (OS) in young non-metastatic RC patients after curative resection.…”
Section: Introductionmentioning
confidence: 99%